дано
m(HNO3) = 189 g
m(Al2O3) - ?
6HNO3+Al2O3-->2AL(NO3)3+3H2O
M(HNO3) = 63 g/moL
n(HNO3) = m(HNO3) / M(HNO3) = 189 / 63 = 3 mol
6n(HNO3) = n(Al2O3)
n(Al2O3) = 3 * / 6 = 0.5 mol
M(Al2O3) = 102 g/mol
m(Al2O3) = n(Al2O3) * M(Al2O3) = 0.5 * 102 = 51 g
ответ 51 гр
Объяснение:
дано
m(HNO3) = 189 g
m(Al2O3) - ?
6HNO3+Al2O3-->2AL(NO3)3+3H2O
M(HNO3) = 63 g/moL
n(HNO3) = m(HNO3) / M(HNO3) = 189 / 63 = 3 mol
6n(HNO3) = n(Al2O3)
n(Al2O3) = 3 * / 6 = 0.5 mol
M(Al2O3) = 102 g/mol
m(Al2O3) = n(Al2O3) * M(Al2O3) = 0.5 * 102 = 51 g
ответ 51 гр
Объяснение: